2020
DOI: 10.1016/j.jeca.2020.e00167
|View full text |Cite
|
Sign up to set email alerts
|

Modelling asymmetric market volatility with univariate GARCH models: Evidence from Nasdaq-100

Abstract: This paper models and estimates the volatility of nonfinancial, innovative and hi-tech focused stock index, the Nasdaq-100, using univariate symmetric and asymmetric GARCH models. We employ GARCH, EGARCH and GJR-GARCH using daily data over the period January 4, 2000 through March 19, 2019. We find that the volatility shocks on the index returns are quite persistent. Furthermore, our findings show that the index has leverage effect, and the impact of shocks is asymmetric, whereby the impacts of negative shocks … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Using univariate asymmetric GARCH models, Aliyev et al (2020) modelled and estimated the volatility of the Nasdaq-100 and found persistent volatility shocks on index returns, a leveraging effect on the index and asymmetric impact of shocks. Zivkov et al (2021) evaluated the multiscale bidirectional volatility spillover effect between national stocks and exchange rate markets among four African countries using the MS-GARCH model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using univariate asymmetric GARCH models, Aliyev et al (2020) modelled and estimated the volatility of the Nasdaq-100 and found persistent volatility shocks on index returns, a leveraging effect on the index and asymmetric impact of shocks. Zivkov et al (2021) evaluated the multiscale bidirectional volatility spillover effect between national stocks and exchange rate markets among four African countries using the MS-GARCH model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, how to accurately predict the volatility of an asset is a very important issue in the actual investment process in the financial field. As to the issue of volatility forecasting, most of literatures used the generalized autoregressive conditional heteroskedasticity (GARCH) family models, a parametric volatility forecasting approach, to predict the volatility of an asset [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Because this type of model can capture most common features of financial assets such as both the linear dependence and strong autoregressive conditional heteroskedasticity (ARCH) effect subsisting on the return series, and both the volatility clustering and leverage effect usually existing at the volatility of financial asset returns series [ 8 , 20 , 21 , 22 , 23 ] (Volatility clustering means that large changes tend to be followed by large changes, of either sign, and small changes tend to be followed by small changes [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding past literatures about volatility forecasting, they tried to use a more flexible model or a complex approach to increase the performance of volatility forecasting [ 15 , 16 , 17 , 19 ]. For example, Aliyev et al [ 12 ] used the GARCH, exponential GARCH (EGARCH) and the GJR-GARCH model of Glosten, Jagannathan and Runkle [ 24 ] models with normal distribution (i.e., the GARCH-N, EGARCH-N and GJR-GARCH-N) to estimate the volatility of the Nasdaq-100. Chun et al [ 14 ] used the above three models, the GARCH-N, EGARCH-N and GJR-GARCH-N, to forecast the volatility in the KOSPI200 in the Korean market.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of literature has studied volatility in some time series variable such as crude oil price (Suleiman et al, 2015Alhassan & Kilishi, 2016Muhammed & Faruk, 2018;Zhang et al, 2019;Nguyen & Walther, 2020;;Boitumelo et al, 2020), exchange rate (Kuhe & Agaigbe, 2018;Abdullah et al, 2017;Okoro & Osisiogu, 2017;Dritsaki, 2019), stock prices (Al Rahahleh & Kao, 2018;Iwada et al, 2018;Lin, 2018;Aliyev et al, 2020), inflation (Fwaga et al, 2017;Nyoni, 2018;Iddrisu et al, 2019) amongst others. Modeling PVCO by some authors has reported varying outcomes over the years.…”
Section: Introductionmentioning
confidence: 99%